EFFECTS OF CARBON EMISSION ON ENVIRONMENTAL QUALITY IN NIGERIA - Mukhtar, Faizah Adhama; Yahaya, Nura Sani; Hayewa, SuleYa'u (Kashere Journal of Management Sciences, 2025)
Nigeria’spursuit of economic growth leads to dependence on fossil fuel as a means of energy generation, in so doingfetching aboutcarbon emission which impacts environmental. As a means of finding solution to this problem, the study examines the effect of CO2 Emissionon environmental quality in country. Secondary data from 1992 to 2022 wasobtained from World Development Indicator (WDI, 2023) and U.S. energy information administration (EIA), 2024. Auto regressive distributive lag model (ARDL) was used as a method of estimation. The outcome reveals confirms strong evidence of cointegration between CO2 Emission on environmental quality. Log run and short run results show energy consumption of petroleum and other liquids relates positively and is significant in determining carbon emission. The study commends that Nigerian policy makers should design and implement sustainable energy policy and technologies in order to reduce carbon emission which is harmful to the environment and make more use of renewable energy such as sunlight, wind, rain, tides, waves, and geothermal heat which are healthier and cleaner choices of energy generation.